Relational dynamics in workshops for siblings of children with developmental disabilities - Vidal, Lutze-Sol Aplaon (2005)
This study attempted to determine the characteristics, needs, emotions, thoughts, and perceptions, of siblings of special children through a series of workshop activities. Ten older siblings, aged 10 to 12 years old, of children with mental retardation and autism were asked to participate in a three-week research-designed workshop of 17 activities. The study was able to successfully describe and explain relational dynamics among the participant-respondents along the five dimensions of knowledge, awareness, acceptance, communication, and plans and recommendations. After the workshop, most of the participants were able to express themselves better and have closer relationships with their parents. They also learned new concepts about special children and became more willing to improve their relationship with their siblings.
"October 2005."
Thesis (M.A. Special Education)--University of the Philippines Diliman.
Keywords: Children with disabilities -- Family relationships -- Philippines -- Quezon City; Autistic children -- Family relationships -- Philippines -- Quezon City; Children with mental disabilities -- Family relationships -- Philippines -- Quezon City